Organophosphorus Poisioning - Still a Challenging Proposition (TAJ: Journal of Teachers Association, 2010)
Organophosphorus poisoning is one of the most common suicidal agents in our country. OP compounds are easily available as it is widely used pesticide. There is no hard restriction on its sale. This cross sectional study was conducted at 250 bedded Pabna District General Hospital between March 2007 to April 2008. A total of 127 patients were studied. Out of which 67 were female and 60 were male. Comorbid conditions like Hepatic, Renal and Cardiac illnesses were excluded from the study. The age of the patients varied from 15-40 years. The conventional method of treatment were given like gastric lavage, oxygen inhalation, IV fluid, oropharyngeal suction etc. Apart from that patients were divided into two groups. Group- A & Group-B. Group -A patients were treated with Inj. Pralidoxim and Inj. Atropine while Group-B were treated with Inj. Atropine alone. Group-A patients revealed recovery rate quicker than Group-B with the improvement of general condition, pupil dilate earlier, pulse attended tachycardia, muscle twitching and fasciculation came to normal in Group A earlier than Group B. Lacrimation and salivation also attained closer to normal in Group B than Group A. The female patients numbered more than the males. DOI: 10.3329/taj.v22i1.5032 TAJ 2009; 22(1): 115-118